Comparison of two ultrashort echo time sequences for the quantification of T1 within phantom and human Achilles tendon at 3 T - Wright, P; Jellus, V; McGonagle, D; Robson, M; Ridgeway, J; Hodgson, R (2012)
Ultrashort echo time (UTE) techniques enable direct imaging of musculoskeletal tissues with short T2 allowing measurement of T 1 relaxation times. This article presents comparison of optimized 3D variable flip angle UTE (VFA-UTE) and 2D saturation recovery UTE (SR-UTE) sequences to quantify T1 in agar phantoms and human Achilles tendon. Achilles tendon T1 values for asymptomatic volunteers were compared to Achilles tendon T1 values calculated from patients with clinical diagnoses of spondyloarthritis (SpA) and Achilles tendinopathy using an optimized VFA-UTE sequence. T1 values from phantom data for VFA- and SR-UTE compare well against calculated T1 values from an assumed gold standard inversion recovery spin echo sequence. Mean T1 values in asymptomatic Achilles tendon were found to be 725 ± 42 ms and 698 ± 54 ms for SR- and VFA-UTE, respectively. The patient group mean T 1 value for Achilles tendon was found to be 957 ± 173 ms (P < 0.05) using an optimized VFA-UTE sequence with pulse repetition time of 6 ms and flip angles 4, 19, and 24°, taking a total 9 min acquisition time. The VFA-UTE technique appears clinically feasible for quantifying T1 in Achilles tendon. T1 measurements offer potential for detecting changes in Achilles tendon due to SpA without need for intravenous contrast agents. Magn Reson Med, 2012. © 2012 Wiley Periodicals, Inc. Copyright © 2012 Wiley Periodicals, Inc.